The Guidance program at Las Piñas College as perceived by the teachers - Diaz, Primitiva A. (Manila : National University, 1994)
The past decade has witnessed some remarkable changes in educational technology particularly in the concept of guidance and in many of its technique.
Chapter 1. The problem and its background -- Chapter 2. Review of related literature and studies -- Chapter 3. Method -- Chapter 4. Presentation, Analysis and interpretation of data -- Chapter 5. Summary, Conclusion and recommendations.
Includes bibliographical references.